Relationship between Mode of Delivery and Frequency and Treatment Outcomes of Congenital Nasolacrimal Dacryostenosis - NUHOĞLU, FADİME; Ozdemir, Fatma Esin; BABAYEV, RUMIL; NUHOĞLU, FADİME; BABAYEV, RUMIL (My University, 2021)
Introduction: The present study evaluates the relationship between the mode of deliveryand the frequency and treatment outcomes of congenital nasolacrimal duct obstruction (CNDO).